Zmiany leśnych zbiorowisk roślinnych w obszarze źródliskowym Tetyńskiej Strugi na Pojezierzu Myśliborskim w ostatnich dekadach (1976–2023) - Smoliga, Aleksander (Leśne Prace Badawcze, 2024)
The aim of this study was to describe the changes in the structure and species composition of forest communities in the Myślibórz Lake District caused by forest management and natural factors. For this purpose, data from phytosociological relevés from the 1960s and 1970s were compared with data collected in the area between 2021 and 2023. A total of 128 relevés were car-ried out at the sites where the forest phytocoenoses had been described several decades earlier. In addition, a dead wood inventory was carried out on 40 circular study plots (0.25 ha). A significant increase in the proportion of common beech ( Fagus sylvatica ), which has been promoted by forest management in recent decades, was observed in the study area. Another tree species whose share in the forest communities has changed significantly is common hornbeam ( Carpinus betulus ). At present, hornbeam is mainly found in the undergrowth. In the past, it formed a complex structure of tree stands together with pedunculate oak ( Quercus robur ) and other deciduous tree species. Common bird cherry ( Padus avium ) is currently gradually re-placing ash ( Fraxinus excelsior ) in the riparian forests. Changes can also be observed in the herb layer. Species that are characteris-tic of individual phytocoenoses are generally less abundant today than they were in the last century. Some species, such as small-balsam (Impatiens parviflora) and water foxtail ( Alopecurus geniculatus ), did not occur in this area in the past. The undergrowth of the tree layer has changed the most, while the herb layer has changed the least. The forest communities of the Myślibórz Lake Dis-trict, especially riparian forests, oak-lime-hornbeam forests and beech forests, have changed considerably in recent decades, mainly due to forest management activities. The largest amount of dead wood has been documented in the riparian forests of this area.